2005
DOI: 10.1167/iovs.04-0607
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Antimicrobial Peptide Expression at the Ocular Surface

Abstract: Together with known lacrimal antimicrobial activities, these results extend the knowledge of antimicrobial activity at an important mucosal site, the ocular surface, allowing synergistic interactions to be investigated. The findings has significant implications both for the understanding of the normal homeostasis of mucosal surfaces and for antimicrobial and anti-inflammatory therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 46 publications
6
60
1
Order By: Relevance
“…2,3,14,18,31-34,36,37 The current study reports for the first time that the epithelial cells of both the cornea and conjunctiva express this important effector of innate immunity. This discovery was initially reported in 2003 51 and has recently been confirmed in a report by Dua et al 52 Our discovery of LL-37 as a part of ocular mucosal defense complements previous studies that have demonstrated that α-defensins hBD-1, -2, and -3 are also secreted by conjunctival and corneal epithelium. 39-43,53 Taken together, these findings suggest that the ocular surface must be added to the growing list of mucosal surfaces throughout the body where multifunctional cationic peptides operate as part of innate immunity.…”
Section: Antiviral Activity Of Ll-37 and Scrambled Ll-37 Against Hsv-supporting
confidence: 83%
“…2,3,14,18,31-34,36,37 The current study reports for the first time that the epithelial cells of both the cornea and conjunctiva express this important effector of innate immunity. This discovery was initially reported in 2003 51 and has recently been confirmed in a report by Dua et al 52 Our discovery of LL-37 as a part of ocular mucosal defense complements previous studies that have demonstrated that α-defensins hBD-1, -2, and -3 are also secreted by conjunctival and corneal epithelium. 39-43,53 Taken together, these findings suggest that the ocular surface must be added to the growing list of mucosal surfaces throughout the body where multifunctional cationic peptides operate as part of innate immunity.…”
Section: Antiviral Activity Of Ll-37 and Scrambled Ll-37 Against Hsv-supporting
confidence: 83%
“…Expression of this defensin is also upregulated in the cornea in response to injury [106] and in the conjunctival epithelium of patients with dry eye [101,107] . Corneal and conjunctival epithelial cells also express hBD-3 [100,101,108] , but while some studies have indicated that expression of this defensin is inducible by TNF-␣ and interferon-␥ [42,43,109] , this was not observed in ocular surface epithelial cells [101] . Whilst McIntosh et al [108] detected expression of hBD-4 in cultured ocular surface cells, this defensin was found only infrequently in non-cultured samples.…”
Section: Amps Present At the Ocular Surfacementioning
confidence: 98%
“…Corneal and conjunctival epithelial cells also express hBD-3 [100,101,108] , but while some studies have indicated that expression of this defensin is inducible by TNF-␣ and interferon-␥ [42,43,109] , this was not observed in ocular surface epithelial cells [101] . Whilst McIntosh et al [108] detected expression of hBD-4 in cultured ocular surface cells, this defensin was found only infrequently in non-cultured samples. Huang et al [110] did not detect hBD-4, -5 or -6 in ocular surface cells.…”
Section: Amps Present At the Ocular Surfacementioning
confidence: 98%
“…This hBD-2 upregulation in response to Pseudomonas aeruginosa might be reduced by the tyrosine kinase inhibitor, but the mechanisms of Pseudomonas aeruginosa-mediated upregulation are not fully understood. Lipopolysaccharide of Pseudomonas aeruginosa is involved in hBD-2 mRNA upregulation in the corneal epithelial cells [14,15]. The upregulation of defensins in the cornea in response to Pseudomonas aeruginosa has also been reported.…”
Section: Introductionmentioning
confidence: 90%